Effects of learning models and instructional media on pencak silat course learning outcomes - Weny Sasmitha; Suwirman Suwirman; Nurul Ihsan; Melaty Melaty; Yuni Utari (Global Econedu, 2026)
This study aims to examine the effect of learning models and instructional media on pencak silat learning outcomes. A 2×2 factorial experimental design was employed with two factors: learning model (blended learning and conventional) and instructional media (video and book/module). Data were analyzed using two-way ANOVA. The results showed that instructional media had a significant effect on learning outcomes (p < 0.05), while the learning model did not (p > 0.05). No interaction effect was found between learning model and instructional media (p > 0.05). These findings indicate that video-based media is more effective than book-based media in improving pencak silat learning outcomes.